ACE2 Expression in Organotypic Human Airway Epithelial Cultures and Airway Biopsies - Chen, Qianyu; Langenbach, Shenna; Li, Meina; Xia, Yuxiu C.; Gao, Xumei; Gartner, Matthew J.; Pharo, Elizabeth A.; Williams, Sinéad M.; Todd, Shawn; Clarke, Nadeene; Ranganathan, Sarath; Baker, Michelle L.; et al. (Frontiers in Pharmacology, 2022)
Coronavirus disease 2019 (COVID-19) caused by infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an acute respiratory disease with systemic complications. Therapeutic strategies for COVID-19, including repurposing (partially) developed drugs are urgently needed, regardless of the increasingly successful vaccination outcomes. We characterized two-dimensional (2D) and three-dimensional models (3D) to establish a physiologically relevant airway epithelial model with potential for investigating SARS-CoV-2 therapeutics. Human airway basal epithelial cells maintained in submerged 2D culture were used at low passage to retain the capacity to differentiate into ciliated, club, and goblet cells in both air-liquid interface culture (ALI) and airway organoid cultures, which were then analyzed for cell phenotype makers. Airway biopsies from non-asthmatic and asthmatic donors enabled comparative evaluation of the level and distribution of immunoreactive angiotensin-converting enzyme 2 (ACE2). ACE2 and transmembrane serine proteinase 2 (TMPRSS2) mRNA were expressed in ALI and airway organoids at levels similar to those of native (i.e., non-cultured) human bronchial epithelial cells, whereas furin expression was more faithfully represented in ALI. ACE2 was mainly localized to ciliated and basal epithelial cells in human airway biopsies, ALI, and airway organoids. Cystic fibrosis appeared to have no influence on ACE2 gene expression. Neither asthma nor smoking status had consistent marked influence on the expression or distribution of ACE2 in airway biopsies. SARS-CoV-2 infection of ALI cultures did not increase the levels of selected cytokines. Organotypic, and particularly ALI airway cultures are useful and practical tools for investigation of SARS-CoV-2 infection and evaluating the clinical potential of therapeutics for COVID-19.